Pseudomonas aeruginosa elastase down-regulates host inflammatory responses by degrading cytokines and chemokines: a non-healing wound perspective - van der Plas, Mariena J. A.; Puthia, Manoj; Ong, Seow Theng; Arkelius, Kajsa; Strömdahl, Ann-Charlotte; Butrym, Marta; Rasmussen, Magnus; Verma, Navin Kumar; Schmidtchen, Artur (Frontiers in Medicine, 2025)
Non-healing venous leg ulcers are characterized by dysfunctional wound healing and frequently exhibit an absence of classical inflammatory signs, despite substantial bacterial loads of the Gram-negative pathogen Pseudomonas aeruginosa. To investigate this clinical observation, we used a porcine wound infection model and complementary in vitro cell and enzymatic activity assays. In vivo, P. aeruginosa infected wounds resulted in attenuated inflammatory responses compared to those infected with Staphylococcus aureus. Protease activity was elevated in P. aeruginosa-infected wounds relative to uninfected controls, while pro-inflammatory cytokine levels decreased over time. In vitro analyses employing cell cultures, wildtype and mutant strains, and clinical isolates from venous ulcers and blood, revealed that P. aeruginosa elastase (LasB) degrades a range of pro-inflammatory cytokines (G-CSF, GM-CSF, IFN-γ, IL-1ra, IL-6, IL-12p40, IL-23, TNF-α) and chemokines (Gro-α, IL-8, IP-10, MCP-1, MIP-1α, MIP-1β) in the extracellular milieu, without impacting cell morphology, transcription factor activation, or subsequent intracellular cytokine production. Correspondingly, wound fluids from non-healing ulcers colonized/infected with P. aeruginosa degraded cytokines, whereas fluids from uninfected wounds did not. Collectively, our findings indicate that P. aeruginosa modulates host inflammation by degrading cytokines and chemokines.